Isolation and Pathogenicity Analysis of a G5P[23] Porcine Rotavirus Strain - Liguo Gao; Hanqin Shen; Sucan Zhao; Sheng Chen; Puduo Zhu; Wencheng Lin; Feng Chen (Viruses, 2023)
(1) Background: Group A rotaviruses (RVAs) are the primary cause of severe intestinal diseases in piglets. Porcine rotaviruses (PoRVs) are widely prevalent in Chinese farms, resulting in significant economic losses to the livestock industry. However, isolation of PoRVs is challenging, and their pathogenicity in piglets is not well understood. (2) Methods: We conducted clinical testing on a farm in Jiangsu Province, China, and isolated PoRV by continuously passaging on MA104 cells. Subsequently, the pathogenicity of the isolated strain in piglets was investigated. The piglets of the PoRV-infection group were orally inoculated with 1 mL of 1.0 × 106 TCID50 PoRV, whereas those of the mock-infection group were fed with an equivalent amount of DMEM. (3) Results: A G5P[23] genotype PoRV strain was successfully isolated from one of the positive samples and named RVA/Pig/China/JS/2023/G5P[23](JS). The genomic constellation of this strain was G5-P[23]-I5-R1-C1-M1-A8-N1-T1-E1-H1. Sequence analysis revealed that the genes VP3, VP7, NSP2, and NSP4 of the JS strain were closely related to human RVAs, whereas the remaining gene segments were closely related to porcine RVAs, indicating a reassortment between porcine and human strains. Furthermore, infection of 15-day-old piglets with the JS strain resulted in a diarrheal rate of 100% (8 of 8) and a mortality rate of 37.5% (3 of 8). (4) Conclusions: The isolated G5P[23] genotype rotavirus strain, which exhibited strong pathogenicity in piglets, may have resulted from recombination between porcine and human strains. It may serve as a potential candidate strain for developing vaccines, and its immunogenicity can be tested in future studies.